Promoting independent learning in the acquisition of English as a foreign language - Salas de Contreras, Luz Marina (Rastros Rostros, 2002)
The main objective of this paper is to look at what "independent learning" means. Furthermore, to present some ways to favor it and finally to participate in an experience of learning English based on autonomy.